Necessary and sufficient conditions of harmonicity of functions of infinitely many variables (Jacobian case) - Feller, M. N. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
A criterion of harmonicity of functions in a Hilbert space is given in the case of weakened mutual dependence of the second derivatives.